Derivative of f(x) g(x) = f '(x) g(x) + f(x) g'(x)
Example: The derivative of x2 sin(x) = 2x sin(x) + x2 cos(x)
Derivative of f(x) / g(x) = ( g(x) f'(x) - f(x) g'(x) ) / (g(x))2
A ditty that helps you remember this rule is "low d high - high d low all over low squared"
Example: The derivative of (2x2-3x-9) / (2x+3) = ((2x+3)(4x-3) - (2x2-3x-9)(2))/(2x+3)2
Derivative of f(x)n = n f(x)n-1 f'(x)
Note that the exponent rule is a special case of the chain rule, which is described in the next section.
Example 1: The derivative of sin3(x) = 3 sin2(x) cos(x)
Example 2: n doesn't need to be a positive integer. It can be a
fraction, or even negative. This can be used to find the derivative of 1/sqrt(x),
which is x-1/2.
The derivative of x-1/2 = (-1/2) x-3/2.
Derivative of f(g(x)) = f'(g(x)) g'(x)
Example: The derivative of tan(sin(x)) = sec2(sin(x)) cos(x)
HMC Mathematics Online Tutorial: The Quotient Rule
Paul's online math notes: The Chain Rule
1728 Software Systems: Product Rule, Quotient Rule, and Chain rule, with examples.
Definition of Continuous
The webmaster and author of this Math Help site is Graeme McRae.